My name is Mina - Almond, David, 1951- (London : Hodder Children's Books, 2013)
Creative, intelligent, nine-year-old Mina keeps a journal in her own disorderly way that reveals how her mind is growing into something extraordinary, especially after she begins homeschooling under the direction of her widowed mother.
5.1
5-8.
5-8
Keywords: Eccentrics and eccentricities -- Juvenile fiction; Families -- England -- Juvenile fiction; Home schooling -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Single-parent families -- Juvenile fiction; Eccentrics and eccentricities -- Fiction; Family life -- Fiction; Home schooling -- Fiction; Mothers and daughters -- Fiction; Single-parent families -- Fiction; Eccentrics and eccentricities -- Fiction; Family life -- England -- Fiction; Home schooling -- Fiction; Mother-daughter relationship -- Fiction; Single-parent families -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction